Climate change impacts on the terrestrial biodiversity and carbon stocks of Oceania - Wardell-Johnson, Grant; Keppel, Gunnar; Sander, Juliane (Surrey Beatty and Sons, 2011)
We review the threats from anthropogenic climate change to the terrestrial biodiversity of Oceania, and quantify decline in carbon stocks. Oceania’s rich terrestrial biodiversity is facing unprecedented threats through the interaction of pervasive environmental threats (deforestation and degradation; introduced and invasive species; fragmentation) and the effects of anthropogenic climate change (sea level rise; altered rainfall patterns and increased fire frequency; temperature rises and increased storm severity, extreme weather events and abrupt system changes). All nine of Oceania’s terrestrial biomes harbour ecosystems and habitat types that are highly vulnerable under climate change, posing an immense conservation challenge. Current policies and management practices are inadequate and the need for new legislation and economic mechanisms is clear, despite powerful interests committed to limiting progress. Mitigation can be achieved by increasing the effectiveness of the protected area network, by maintaining and effectively managing existing carbon stocks and biodiversity, and by reforestation to sequester atmospheric carbon. A price on carbon emissions may encourage less carbon-intensive energy use while simultaneously encouraging reforestation on long-cleared land, and reducing degradation of native forests. However, realizing these changes will require societal change, and depend on input and collaboration from multiple stakeholders to devise and engage in shared, responsible management.